2012
DOI: 10.2215/cjn.09620911
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction and Elevated Blood Pressure in Long-Term Childhood Cancer Survivors

Abstract: SummaryBackground and objectives Little is known about renal function and blood pressure (BP) in long-term childhood cancer survivors. This cross-sectional study evaluated prevalence of these outcomes and associated risk factors in long-term childhood cancer survivors at their first visit to a specialized outpatient clinic.Design, Setting, Participants, & Measurements Estimated GFR; percentages of patients with albuminuria, hypomagnesemia, and hypophosphatemia; and BP were assessed in 1442 survivors $5 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 36 publications
8
87
3
Order By: Relevance
“…As in line with our results, previous cross-sectional studies showed that higher ifosfamide and cisplatin doses, and nephrectomy were associated with diminished GFR (12)(13)(14)18). Moreover, we observed that HD-cyclophosphamide was related with a lower GFR, but not with a GFR <90 mL/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As in line with our results, previous cross-sectional studies showed that higher ifosfamide and cisplatin doses, and nephrectomy were associated with diminished GFR (12)(13)(14)18). Moreover, we observed that HD-cyclophosphamide was related with a lower GFR, but not with a GFR <90 mL/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Recently, we showed in a large cross-sectional cohort study, including 1,442 CCS with a median followup of 12 years after diagnosis, that 28% had 1 renal late effect (s), of whom, 62 (4.6%) developed glomerular dysfunction (GFR <90 mL/min/1.73 m 2 ). Higher ifosfamide, cisplatin, and carboplatin dose, high-dose (HD-)cyclophosphamide, nephrectomy, and longer follow-up were identified as risk factors for glomerular dysfunction (18).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension was present in 23%, which is relatively high compared with previous findings of 14% and 19% among childhood survivors; this finding could be explained by the fact that survivors were older and follow-up time was longer in the current study (28,45,46). This percentage was even higher (31%) in survivors treated with unilateral nephrectomy.…”
Section: Discussioncontrasting
confidence: 70%
“…However, in these studies, follow-up time was relatively short, and patient numbers were small. A recent study in a large cohort of childhood cancer survivors 12 years after diagnosis described nephrectomy and the combination of nephrectomy with abdominal radiotherapy as risk factors for renal damage, represented by hypertension, proteinuria, and reduced glomerular function (28). In the present study, with a median follow-up of 18 years, we showed that nephrectomy and the combination of nephrectomy with abdominal radiotherapy were associated with a decreased glomerular function and albuminuria but not tubular dysfunction.…”
Section: Discussionsupporting
confidence: 66%
“…A Dutch study of 1442 CCS demonstrated that survivors who had undergone nephrectomy had an almost 9-fold increase in their risk for diminished renal function [as measured by glomerular filtration rate (GFR)]. 18 A second study of 763 adult CCS demonstrated that nephrectomy increased the risk for decreased glomerular function, although most survivors maintained their GFR within the normal range. 19 There was also a higher risk for hypertension among those survivors treated with nephrectomy-almost a third had elevated blood pressure.…”
Section: Nephrectomymentioning
confidence: 99%